1991
DOI: 10.1128/aac.35.12.2473
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial spectrum of sparfloxacin and its activities alone and in association with other drugs against Mycobacterium avium complex growing extracellularly and intracellularly in murine and human macrophages

Abstract: The MICs and MBCs of the new difluorinated quinolone drug sparfloxacin against type strains belonging to 21 species of mycobacteria were screened. The MICs and MBCs were within the range of 0.1 to 2.0 and 0.1 to 4.0 ,ug/ml, respectively (with an MBC/MIC ratio of 1 to 2), and against 18 of the 21 species tested, the drug showed significant bactericidal activity (at least 99% killing or more of the initial inoculum added) at concentrations well within the reported peak concentrations in serum (Cm.) in humans. MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…In support of the use of such models, a good correlation has previously been reported between the use of murine bone marrow-derived macrophages and the use of human monocytes for the evaluation of the bactericidal effects of therapeutic compounds (34). Moreover, studies that used different sources of macrophages (32,44) observed that compounds which are very active in broth also tended to be active in the macrophage cultures.…”
Section: Discussionmentioning
confidence: 90%
“…In support of the use of such models, a good correlation has previously been reported between the use of murine bone marrow-derived macrophages and the use of human monocytes for the evaluation of the bactericidal effects of therapeutic compounds (34). Moreover, studies that used different sources of macrophages (32,44) observed that compounds which are very active in broth also tended to be active in the macrophage cultures.…”
Section: Discussionmentioning
confidence: 90%
“…The Public Health Service Task Force on Prophylaxis and Therapy for MAC recently recommended clarithromycin (CLA)-containing regimens for therapy for disseminated infections by these organisms in AIDS patients (20). At the present time, only for a few reports has the activity of CLA-containing combinations been studied, by in vitro and ex vivo methods, on the same strains (27,28).In this study, we assessed the susceptibility of MAC strains isolated in Italy from AIDS patients (7) by determining the MICs of eight antimicrobial agents both by the radiometric method (11) and by a model of human monocyte-derived MP infection (22,23). This was adopted to evaluate the relationship between the extracellular and intracellular activities of drugs with different capacities for accumulating within MP (31).…”
mentioning
confidence: 99%
“…The colony-forming units (CFU) were enumerated after about 4 days of the Petri dishes incubation at 37°C. As described by Rastogi et al (1991), this treatment with 0.25% (w/v) SDS did not affect the viability of mycobacteria. The results were compared with the growth of the bacilli in the control culture (untreated macrophages).…”
Section: Intracellular Antimycobacterial Activity Of Ethanol Plant Exmentioning
confidence: 99%
“…After phagocytosis, the medium from each well was retired and the cells were then treated during 1 h by a medium containing 10 µg/ml of amikacin. This treatment was followed by several changes of hanks balanced salt solution to remove all extracellular M. smegmatis MC2 (Rastogi et al, 1987(Rastogi et al, , 1991Sharbati-Tehrani et al, 2005). (iii) Treatment by plant ethanol extract: About 5 h after infection, necessary time of phagocytosis and elimination of extracellular M. smegmatis MC2, the ethanol leaves plant extract (6.02 ± 0.76 mg/ml) which was solubilized in RPMI-1640 as demonstrated above, was added to the wells containing infected macrophages.…”
Section: Intracellular Antimycobacterial Activity Of Ethanol Plant Exmentioning
confidence: 99%
See 1 more Smart Citation